cis- and trans-acting elements involved in reactivation of vaccinia virus early transcription. - Masternak, K (1996)
We have previously shown that transcription from the vaccinia virus 7.5K early promoter is reactivated late in infection (J. Garcés, K. Masternak, B. Kunz, and R. Wittek, J. Virol. 67:5394-5401, 1993). To identify the sequence elements mediating reactivation, we constructed recombinant viruses harboring deletions, substitutions, or insertions in the 7.5K promoter or its flanking regions. The analysis of these viruses showed that sequences both upstream as well as downstream of the transcription initiation site contribute to reactivation of the 7.5K promoter. We tested whether reactivation could be explained by a high affinity of vaccinia virus early transcription factor to reactivated promoters. Bandshift experiments using purified protein showed that promoters which bind the factor with high affinity in general also have high early transcriptional activity. However, no correlation was found between affinity of the factor and reactivation. Interestingly, overexpression of recombinant early transcription factor in vaccinia virus-infected cells resulted in a shutdown of late transcription and in reactivation of promoters, which are normally not reactivated.